2013
DOI: 10.1155/2013/397087
|View full text |Cite
|
Sign up to set email alerts
|

Tuberous Sclerosis Associated with Polycystic Kidney Disease: Effects of Rapamycin after Renal Transplantation

Abstract: Tuberous sclerosis is rarely associated with autosomal dominant polycystic kidney disease in the so-called tuberous sclerosis complex. This association leads to an increased frequency of end-stage renal disease. We present a patient suffering from both syndromes, who received a renal graft and anticalcineurinic drugs as immunosuppressive agents. Progressive titration of the drug was necessary in order to attain the effective doses due to the enzymatic induction caused by concomitant treatment with antiepilepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Abdominal distention and hypertension are common manifestations of ADKPD in these cases 6. Progression to end-stage renal disease (ESRD) has been noted in early ages, even as early as the third decade in some cases, and requires renal replacement therapy 4 11 17 21 22. According to Sampson et al , most patients with non-mosaic deletions in TSC1/PKD2 gene were found to have enlarged cystic kidneys during infancy or childhood with features of advanced ADPKD at the time of diagnosis, but other patients had variable degrees of renal involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal distention and hypertension are common manifestations of ADKPD in these cases 6. Progression to end-stage renal disease (ESRD) has been noted in early ages, even as early as the third decade in some cases, and requires renal replacement therapy 4 11 17 21 22. According to Sampson et al , most patients with non-mosaic deletions in TSC1/PKD2 gene were found to have enlarged cystic kidneys during infancy or childhood with features of advanced ADPKD at the time of diagnosis, but other patients had variable degrees of renal involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Rosado et al [17] presented regression of cardiac rhabdomyomas, reduction in size of abdominal tumors, and improvement of cysts in native kidneys after switching from tacrolimus to rapamycin because of calcineurin inhibitor nephrotoxicity. All of these patients were converted some time after transplantation, whereas we presented the first case of intended rapamycin application at the time of kidney transplantation [18].…”
Section: Discussionmentioning
confidence: 99%
“…Polycystic kidney disease is reported to cause end-stage renal disease in patients with tuberous sclerosis 11 12. and is frequently complicated by chronic renal failure 23. A CT scan or an ultrasound of the abdomen is almost always sufficient to diagnose polycystic kidney disease due presence of some specific features.…”
Section: Discussionmentioning
confidence: 99%